(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Pure water and clean air is the fundamental right of the every citizen of India given by the constitution, but the current scenario is that the contamination of surface water, ground water is going to new heights. So, our study focuses the present contamination scenario of river Ganga water. Our government specially concern agencies can take the serious steps to control the water pollution. In this study, we cover the physic-chemical and microbial parameters to analyze the water quality.Water pollution is a major global problem. It requires ongoing evaluation and revision of water resource policy at all levels (international down to individual aquifers and wells). It has been suggested that water pollution is the leading worldwide cause of death and diseases, and that it accounts for the deaths of more than 14,000 people daily.